Interfacial Ion‐Trapping Electrolyte‐Gated Transistors for High‐Fidelity Neuromorphic Computing. (14th March 2022) - Jin, Minho; Lee, Haeyeon; Im, Changik; Na, Hyun‐Jae; Lee, Jae Hak; Lee, Won Hyung; Han, Junghyup; Lee, Eungkyu; Park, Junwoo; Kim, Youn Sang
Abstract: Li + electrolyte‐gated transistors (EGTs) have received much attention as artificial synapses for neuromorphic computing. EGTs, however, have been still challenging to achieve long‐term synaptic plasticity, which should be linearly and symmetrically controlled with the magnitude of electrical potential at the gate electrode. Herein, a fluoroalkylsilane (FAS) self‐assembled monolayer (SAM) is introduced as a channel‐electrolyte interlayer with the function of sequential ion‐trapping in Li + EGTs. It is demonstrated that the retention of Li + ions can be enhanced, resulting in stable non‐volatile channel conductance update with high fidelity, linearity, and symmetry in EGTs treated with FAS with 5 fluoroalkyl chains. Through investigating electrical analysis and chemical analysis, it is verified that fluoroalkyl chains enable the sequential ion‐trapping at the channel‐electrolyte interface by coulombic attraction between Li + ions and fluorocarbons. Simulations of artificial neural networks using 20 × 20 digits show FAS‐treated EGTs are suitable as artificial synapses with an accuracy of 89.71% by identical gate pulses and 91.97% by non‐identical gate pulses. A methodological approach is newly introduced for developing synaptic devices based on EGTs for neuromorphic computing with high fidelity. Abstract : The fluoroalkyl chains of the fluorinated self‐assembled monolayer can sequentially trap and de‐trap Li + ions by an electric field. Due to trapped Li + ions, the non‐volatile channel current appears in the electrolyte‐gated transistor (EGT). The sequential ion‐trapping effect in EGT enables channel conductance update with high linearity and symmetry, confirming that EGTs with ion‐trapping interlayer are suitable for high‐fidelity neuromorphic computing.